Exploring Arabic speakers’ perceptions of EAP reading: Cross-linguistic effects on processing and strategy use - Kavanagh, Anne (2014)
Higher education studies, particularly at postgraduate level, are characterised by heavy reading loads which can be challenging for all students, but especially for those studying in a second language. This paper focuses on a group of Arabic-speaking international students studying on a British university-based presessional EAP programme to explore their perceptions of the difficulties they encounter and the strategies they employ when reading in English. Data was gathered in two phases in which the Phase 1 questionnaire results provided a basis for the Phase 2 semi-structured interviews. The resulting case studies revealed varying confidence levels, frequent use of context-level processing strategies, limited use of word-level strategies, automatic reliance on context, and gaps in phonological, orthographic and morpho-syntactic knowledge of English. Pedagogical implications and recommendations include the need for practitioners to pay more specific attention to language needs in order to develop lower-level processing strategies that increase efficiency and effectiveness in L2 reading, thus addressing these gaps in Arabic-speakers’ linguistic knowledge of English.